2014
DOI: 10.1007/s10147-014-0723-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect on HPV vaccination in Japan resulting from news report of adverse events and suspension of governmental recommendation for HPV vaccination

Abstract: Our results should help in understanding the need for a strong promotion of vaccine usage and cancer screening after future retraction of the recommendation suspension. This may apply to other countries with an unsatisfactory rate of HPV vaccination due to fears of adverse vaccine events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…In June 2013, the Japanese government temporarily suspended the active promotion of the HPV vaccination program because of adverse reactions, and this has not yet resumed [9]. Morimoto et al reported that this suspension reduced the coverage of the first dose of the HPV vaccination by 97% in June 2013, compared with the same month in is officially published) [10]. These situations in Japan might result in increasing CC mortality rate among young women.…”
Section: Introductionmentioning
confidence: 97%
“…In June 2013, the Japanese government temporarily suspended the active promotion of the HPV vaccination program because of adverse reactions, and this has not yet resumed [9]. Morimoto et al reported that this suspension reduced the coverage of the first dose of the HPV vaccination by 97% in June 2013, compared with the same month in is officially published) [10]. These situations in Japan might result in increasing CC mortality rate among young women.…”
Section: Introductionmentioning
confidence: 97%
“…Since April 2013, the bivalent and quadrivalent vaccines (Cervarix and Gardasil) have been included in the national immunization program. However, due to potential adverse effects of HPV vaccination, such as chronic pain, the proactive recommendation for vaccination was suspended in June 2013 (Morimoto et al 2014;Ueda et al 2015;Hanley et al 2015). The Vaccine Adverse Review Committee of the Japanese Ministry of Health investigated adverse events in about 8,898,000 injections from 2010 to 2013.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 In early spring of the same year, media coverage about these adverse events was frequent and the vaccination rate for HPV decreased dramatically. 15 Our results might reflect mothers' wishes to avoid risk even if the risk of an adverse event is slight. Therefore, if new combination vaccines are introduced in Japan, the risk of adverse events is an important factor for mothers.…”
Section: Discussionmentioning
confidence: 74%